2000
DOI: 10.1002/chin.200030250
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Stability Issues of Cu(In,Ga)Se2‐Based Solar Cells

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In addition, impurity diffusion and changes in doping profiles may affect device stability (Batzner et al, 2004;Degrave et al, 2001), but the industry has resolved this problem by using special alloys. CIGS has a flexible structure that enhances its tolerance to chemical changes and because of this it has been previously argued that copper atoms do not pose stability problems for CIGS cells (Guillemoles et al, 2000). Damp heat tests performed on unencapsulated CIGS cells have indicated that humidity degrades cell performance and is more obvious as V OC and FF degradation due to the increased concentration of deep acceptor states in the CIGS absorber (Schmidt et al, 2000).…”
Section: Pv Degradationmentioning
confidence: 99%
“…In addition, impurity diffusion and changes in doping profiles may affect device stability (Batzner et al, 2004;Degrave et al, 2001), but the industry has resolved this problem by using special alloys. CIGS has a flexible structure that enhances its tolerance to chemical changes and because of this it has been previously argued that copper atoms do not pose stability problems for CIGS cells (Guillemoles et al, 2000). Damp heat tests performed on unencapsulated CIGS cells have indicated that humidity degrades cell performance and is more obvious as V OC and FF degradation due to the increased concentration of deep acceptor states in the CIGS absorber (Schmidt et al, 2000).…”
Section: Pv Degradationmentioning
confidence: 99%
“…On the laboratory scale, power conversion efficiencies of over 20% have been achieved by partial substitution of gallium for indium . This outstanding performance, which is partly due to advantageous properties for solar cell applications, such as direct band gap transitions and high absorption coefficients, and their high material stability, including exceptional radiation hardness, , has evoked the widespread commercialization prospects of Cu x (In 1‑ y Ga y )(Se 1‑ z S z ) 2 (CIGSeS) based solar cells. Besides, the ability to tune the band gap energies E g in the range from 1.0 to 2.4 eV by adjusting their composition (from y = z = 0 to y = z = 1) , makes a multijunction (tandem) solar cell feasible as an approach to surpass the current limits of CIGSeS cell efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Copper chalcogenides (CuSe, CuS) and their ternary (CuInSe 2 , CuGaSe 2 , CuInS 2 ) and quartenary compounds (Cu(In 1− x Ga x )Se 2 , CuIn(Se 1−x S x ) 2 ) have attracted much interest in recent years owing to their outstanding electro-optical properties. Among them, the I−III−VI 2 chalcopyrite semiconductors are among the most promising light-absorbing materials for photovoltaic applications because of their suitable band gaps, high absorption coefficients, and good radiation stabilities. Thin-film solar cells of Cu(In 1− x Ga x )Se 2 have achieved record conversion efficiencies as high as 21.5% . Chalcopyrite CuInSe 2 , with a direct band gap of ∼1.04 eV, has a high absorption coefficient over the UV−vis range, which is on the order of 10 5 cm −1 for the bulk and 10 4 cm −1 for thin films. , In order to achieve a better match to the solar spectrum, it is desirable to widen the band gap of CuInSe 2 by about 0.2−0.5 eV.…”
mentioning
confidence: 99%